Chromogenic Assay Is More Efficient in Identifying α-Amylase Inhibitory Properties of Anthocyanin-Rich Samples When Compared to the 3,5-Dinitrosalicylic Acid (DNS) Assay - Sadia Zulfiqar; Federica Blando; Caroline Orfila; Lisa J. Marshall; Christine Boesch (Molecules, 2023)
The inhibition of carbohydrate digestion by plant bioactive compounds is a potential dietary strategy to counteract type 2 diabetes. Indeed, inhibition of α-amylase, a key enzyme that carries out the bulk of starch digestion, has been demonstrated for a range of bioactive compounds including anthocyanins; however, sample pigmentation often interferes with measurements, affecting colorimetric assay outcomes. Therefore, the present study compared the performance of a direct chromogenic assay, using 2-chloro-4 nitrophenyl α-D-maltotrioside (CNPG3) as a substrate, with the commonly used 3,5-dinitrosalicylic acid (DNS) assay. The direct chromogenic assay demonstrated a 5–10-fold higher sensitivity to determine α-amylase inhibition in various samples, including acarbose as a reference, pure anthocyanins, and anthocyanin-rich samples. The IC50 values of acarbose presented as 37.6 μg/mL and 3.72 μg/mL for the DNS assay and the direct chromogenic assay, respectively, whereas purified anthocyanins from blackcurrant showed IC50 values of 227.4 µg/mL and 35.0 µg/mL. The direct chromogenic assay is easy to perform, fast, reproducible, and suitable for high-throughput screening of pigmented α-amylase inhibitors.